Healthy Drinks, Healthy Teeth - Ciunerkaq Tanqigtuq (The Future is Bright): A study protocol for a community-based, non-randomized sociobehavioral trial to reduce added sugar intake in Alaska Native Yup'ik children in the Yukon-Kuskokwim Delta - Chi, Donald L; Lewis, Frances Marcus; Weinstein, Philip; Mancl, Lloyd; Milgrom, Peter; Edwards, Todd; Coldwell, Susan; O'Brien, Diane; Bersamin, Andrea; Hopkins, Scarlett; Orr, Eliza; Rivera, Patricia; et al. (Contemporary Clinical Trials, 2024)
BACKGROUND: This study protocol describes a community-based intervention that will seek to reduce added sugar intake in Yup'ik Alaska Native children by targeting reductions in sugar-sweetened fruit drinks. METHODS: A two-group non-randomized design will be used to evaluate the intervention in three Yup'ik communities in Alaska focusing on children age 1 to less than age 12 years with a minimum enrollment target of 192 children. Families in the intervention arm will participate in a program consisting of five sessions plus four brief check-ins, all delivered by a Yup'ik Community Health Worker. Modifications to the local store environment will be made to give families a place to purchase sugar-free water enhancers. Families in the delayed treatment control arm will receive no intervention during the main study period. There will be five data collection visits (baseline, 1-month, 3-months, 6-months, and 12-months) that will include collection of survey and dietary data, and a hair and plaque sample from each participating child. The outcomes will be change, from baseline to 6 months, in added sugar intake based on a validated hair biomarker (grams of added sugar/day). We hypothesize children in the intervention arm will have greater reductions in added sugar intake compared to children in the control arm as measured by the hair biomarker. DISCUSSION: This is one of the first known community-based sociobehavioral interventions aimed specifically at reducing added sugar intake in Alaska Native communities by targeting sugar-sweetened fruit drinks. TRIAL REGISTRATION: ClinicalTrials.govNCT05219448 (first posted on February 2, 2022).